PERBEDAAN INVOLUSI UTERI PADA IBU POST PARTUM NORMAL YANG DIBERI DANTIDAK DIBERI TERAPI RELAKSASI HYPNOBIRTHING - Wulan Sari, Novi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Postpartum bleeding is one of the problems in post partum mothers. 7 out of 10pregnant women who will do labor feel anxiety, this is because mother trauma because ofpain during previous delivery. Treatment to overcome postpartum hemorrhage is by doinghypnobirthing relaxation therapy techniques that can stimulates the release of thehormone oxytocin causing uterine contractions so that the process of uterine involution,especially the decrease in fundal uterine height (TFU), can run normally. The purpose ofthis study was to investigate the difference in uterine involution given and not givenhypnobirthing relaxation therapy in normal post partum mother.This research wasconducted by using Quasi Experimental research type with Equivalent Time SampleDesign design. This research was conducted at BPS Hj. YL Kecamatan Lubuk AlungPadang Pariaman with a sample of 18 people pregnant women. 6 mothers for treatmentand 12 mothers were controlled. Data processing with univariate and bivariate dataanalysis using independent T-test. The results obtained for day 1 Pvalue (0.001) <a (0.05)then there is influence of hypnobirthing relaxation therapy on uterine involution on postpartum mother, and on day k 7 Pvalue (0,180)> a (0,05) hence absence the effect ofhypnobirthing relaxation therapy on uterine involution on post partum mothers. It can beconcluded that the effect of hypnobirthing relaxation therapy on uterine involution innormal postpartum mothers day 1 and no effect of hypnobirthing relaxation therapy onuterine involution in normal 7-day postpartum motherKeywords: uterine involution, hypnobirthing